Importance of decolonising western languages in South African opera schools in higher education: a content analysis - Yende, Sakhiseni Joseph; Rostislava, Pashkevitch (African Perspectives of Research in Teaching & Learning (APORTAL), 2022)
Concepts such as decolonisation, Africanisation, indigenisation, and internationalisation of curricula have become a centre of discourse in South African institutions of higher education. Even though the debate on decolonisation of Western curricula has become an epicentre, South African opera schools continue to be dominated by Western orthodoxy. In South African opera schools, the decolonisation of the Western language agenda has not been successfully addressed as many South African opera schools continued to prioritise Western languages, such as German, Italian, and French. In contrast, African languages continue to be neglected. This neglect is attributed to the problem that South African higher education institutions are dominated by Western orthodoxy. A clear need exists for the decolonisation of the curricula from Western Eurocentric languages to African languages. Therefore, this article aims to critically discuss and raise awareness of the importance of decolonising Western orthodoxy in South African opera schools in higher education. A qualitative research method was adopted with content analysis as the primary methodology. This article also used a combination of a myth of decolonisation theory and decolonialwashing theory to urge that decolonisation is a buzzword in South African opera schools. The findings of this article were presented in the following three significant themes: 1. Relevance of African languages; 2. Advantages of using African languages; 3. Challenges faced by South African opera schools. The findings of this article revealed that it is important for South African opera schools to have musical arts programmes that promote and cultivate the marginalised values of the African people. This article concludes by recommending that there is a collective effort that must take place to ensure that decolonisation becomes a reality rather than a myth in South African higher education.
Journal article published in African Perspectives of Research in Teaching & Learning Journal (APORTAL) Vol 6 (2) (2022)
Keywords: African languages; Curricula; Decolonisation; Higher education; Opera schools; Education, Higher; Education -- Curricula -- South Africa; Decolonization -- South Africa